The darker side of Western modernity global futures, decolonial options - Mignolo, Walter (Durham Duke University Press, 2011)
During the Renaissance and the Enlightenment, coloniality emerged as a new structure of power as Europeans colonized the Americas and built on the ideas of Western civilization and modernity as the endpoints of historical time and Europe as the center of the world. Walter D. Mignolo argues that coloniality is the darker side of Western modernity, a complex matrix of power that has been created and controlled by Western men and institutions from the Renaissance, when it was driven by Christian theology, through the late twentieth century and the dictates of neoliberalism. This cycle of coloniality is coming to an end. Two main forces are challenging Western leadership in the early twenty-first century. One of these, “dewesternization,” is an irreversible shift to the East in struggles over knowledge, economics, and politics. The second force is “decoloniality.” Mignolo explains that decoloniality requires delinking from the colonial matrix of power underlying Western modernity to imagine and build global futures in which human beings and the natural world are no longer exploited in the relentless quest for wealth accumulation.
Includes bibliographical references and index.
Keywords: Civilization, Western